Motor Polyneuropathy in an Adult Dog : Case Report - Fonseca, Giordano Zoega Martins; Bernardes, Giselle de Lima; Bahr Arias, Mônica Vicky (Acta Scientiae Veterinariae, 2023)
Background: Nonambulatory flaccid tetraparesis can be the result of diseases of the peripheral nervous system and it is characterized by generalized lower motor neuron (LMN) signs, as weakness, tetraparesis/tetraplegia, decreased muscle tone and reflexes. The term polyneuropathy is used for dysfunction of multiple peripheral nerves. In Brazil, there are several etiologies for polyneuropathy in dogs, such as acute idiopathic polyradiculoneuritis, botulism and myasthenia gravis. Toxoplasma gondii is an uncommon cause of LMN diseases in dogs. The aim of this report was to describe a case of flaccid tetraplegia toxoplasmosis in an adult dog with a Toxoplasma gondii serology with a markedly elevated IgG titer of 1:4096. Case: A 4-year-old intact mongrel male dog, weighing 19.6 kg, was referred to the Veterinary Medical Teaching Hospital of the Universidade Estadual de Londrina (UEL) with a 5-day history of weakness that progressed to tetraparesis. Physical examination revealed no significant changes other than the dull and unkempt coat. Neurologic examination revealed severe tetraparesis that was worse in the pelvic limbs, with decreased muscle tone in all four limbs. Postural reactions and the interdigital reflex were absent in all four limbs, as was the patellar reflex, but pain perception was present. There were no clinical signs of dysfunction on examination of the cranial nerves. Laboratory tests were performed, and creatine kinase was elevated (819 U/L). Blood was drawn to look for antibodies to Toxoplasma gondii and Neospora caninum class IgG using the indirect immunofluorescence technique. The antibody titer for Toxoplasma gondii (IgG) was 1:4096. A chest radiograph was performed to look for megaesophagus, and a pulmonary pattern suggestive of mild diffuse pneumonia was observed. Treatment was performed with sulfamethoxazole and trimethoprim, and the dog’s condition improved slightly. Discussion: Based on lower motor neuron findings, the neurologic lesion was localized in the nerve roots, peripheral nerves, neuromuscular junctions, and muscles. The most important diseases in the list of differential diagnoses were immune-mediated or infectious polyradiculoneuritis (toxoplasmosis, neosporosis), myasthenia gravis, toxic polyneuropathy (botulism, chronic organophosphate poisoning), and paraneoplastic polyneuropathy. Among these differential diagnoses, polyradiculoneuritis is one of the most common. It is an idiopathic inflammatory disease. Exposure to raccoon saliva (in the U.S.), vaccination, or infection have been proposed as precipitating causes, but the triggers of this disease remain unknown. Serology for neosporosis was negative, while IgG titers for toxoplasmosis were 1:4096. In a previous study, dogs with acute polyradiculoneuritis were more likely to have T. gondii IgG serum antibody titers than dogs without neurologic signs. Infection with the protozoa T. gondii and N. caninum can cause intense polyradiculoneuritis in dogs accompanied by myositis, especially in puppies. One treatment trial was based on the administration of sulfonamide-trimethoprim with pyrimethamine, whose efficacy in the treatment of toxoplasmosis in dogs has also been reported in the literature. Neurologic deficits improved slightly, and there is a possibility that certain signs may not disappear completely because of the permanent damage caused by inflammation of the nervous system, as observed in the present case. The case had the limitation that it was not possible to perform other laboratory tests to demonstrate histopathologically the presence of Toxoplasma gondii organisms in muscles or nerves. Recovery of normal function is less likely in protozoan polyradiculoneuritis than in noninfectious polyradiculoneuritis. Thus, in the present case, the main suspicion was polyradiculoneuritis secondary to toxoplasmosis. Although it is a rare condition, it is important to consider toxoplasmosis in dogs with LMN-type tetraparesis or tetraplegia. Keywords: polyneuropathy, polyradiculoneuritis, tetraparesis, dogs, peripheral nervous system. Título: Polineuropatia motora em cão adulto Descritores: polineuropatia, polirradiculoneurite, tetraparesia, cães, sistema nervoso periférico.